L type Ca2+ channel blockers prevent oxaliplatin-induced cold hyperalgesia and TRPM8 overexpression in rats - Kawashiri Takehiro; Egashira Nobuaki; Kurobe Kentaro; Tsutsumi Kuniaki; Yamashita Yuji; Ushio Soichiro; Yano Takahisa; Oishi Ryozo (Molecular Pain, 2012)
Abstract Background Oxaliplatin is an important drug used in the treatment of colorectal cancer. However, it frequently causes severe acute and chronic peripheral neuropathies. We recently reported that repeated administration of oxaliplatin induced cold hyperalgesia in the early phase and mechanical allodynia in the late phase in rats, and that oxalate derived from oxaliplatin is involved in the cold hyperalgesia. In the present study, we examined the effects of Ca2+ channel blockers on oxaliplatin-induced cold hyperalgesia in rats. Methods Cold hyperalgesia was assessed by the acetone test. Oxaliplatin (4 mg/kg), sodium oxalate (1.3 mg/kg) or vehicle was injected i.p. on days 1 and 2. Ca2+ (diltiazem, nifedipine and ethosuximide) and Na+ (mexiletine) channel blockers were administered p.o. simultaneously with oxaliplatin or oxalate on days 1 and 2. Results Oxaliplatin (4 mg/kg) induced cold hyperalgesia and increased in the transient receptor potential melastatin 8 (TRPM8) mRNA levels in the dorsal root ganglia (DRG). Furthermore, oxalate (1.3 mg/kg) significantly induced the increase in TRPM8 protein in the DRG. Treatment with oxaliplatin and oxalate (500 μM for each) also increased the TRPM8 mRNA levels and induced Ca2+ influx and nuclear factor of activated T-cell (NFAT) nuclear translocation in cultured DRG cells. These changes induced by oxalate were inhibited by nifedipine, diltiazem and mexiletine. Interestingly, co-administration with nifedipine, diltiazem or mexiletine prevented the oxaliplatin-induced cold hyperalgesia and increase in the TRPM8 mRNA levels in the DRG. Conclusions These data suggest that the L type Ca2+ channels/NFAT/TRPM8 pathway is a downstream mediator for oxaliplatin-induced cold hyperalgesia, and that Ca2+ channel blockers have prophylactic potential for acute neuropathy.